The use of physically constraining tools for grip-specific skill development in racket, stick and club sports: A scoping review - Busuttil, N. A., Roberts, A. H.; Dunn, M.; Connolly, M.; Middleton, K. J. (Journal of Sports Sciences, 2023)
Coaches use physically constraining tools to supplement their coaching when developing sport-specific skills, however, their effectiveness is unknown. This scoping review aimed to understand the efficacy of physically constraining tools used in racket, stick, and club sports for grip-specific skill development. This scoping review followed the Joanna Briggs Institute methodology and PRISMA guidelines. Peer-reviewed research, including quasi-experimental, true-experimental, case studies, and grey literature were considered. Peer-reviewed sources were searched on Web of Science, Medline, and SPORTDiscus until October 6th, 2022. Exclusion criteria were (1) not original peer-reviewed research; (2) disabled participants or used for rehabilitation; or (3) not available in English. Data extracted were the type of tool, research foci, measures, and outcomes of the tool`s efficacy. Zero peer-reviewed sources were identified on the efficacy of using physically constraining tools for grip-specific skill development. Common trends identified from the excluded sources were explored to provide a basis for the importance of using physically constraining tools for grip-specific skill development. Many tools are used in coaching despite their unclear efficacy, however, the current results can guide future work to assess the acute and longitudinal effects of using these tools, specifically within the development and performance of sport-specific skills.